On the idea of complexes of theories in the cognitive sciences. - Sushchin, Mikhail (Synthese, 2025)
In this article, I develop the idea of theoretical complexes to characterize large-scale theoretical movements in the cognitive sciences, such as classical computational cognitivism, connectionism, embodied cognition, and predictive processing. It is argued that these theoretical movements should be construed as groups of closely connected individual theories and models of cognitive processes that share similar general hypotheses about the nature of cognition. General hypotheses form conceptual cores of complexes of cognitive theories, giving them their structure and functional properties. The latter are said to consist primarily of helping practitioners of theoretical complexes further develop their individual accounts of cognitive phenomena. It is claimed that the theoretical diversity fostered in this way has already benefited the cognitive sciences in a number of important ways and has the potential to further advance the field.